2007
DOI: 10.1371/journal.pmed.0040298
|View full text |Cite
|
Sign up to set email alerts
|

Patient Retention in Antiretroviral Therapy Programs in Sub-Saharan Africa: A Systematic Review

Abstract: BackgroundLong-term retention of patients in Africa's rapidly expanding antiretroviral therapy (ART) programs for HIV/AIDS is essential for these programs' success but has received relatively little attention. In this paper we present a systematic review of patient retention in ART programs in sub-Saharan Africa.Methods and FindingsWe searched Medline, other literature databases, conference abstracts, publications archives, and the “gray literature” (project reports available online) between 2000 and 2007 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

54
686
15
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 679 publications
(758 citation statements)
references
References 17 publications
54
686
15
3
Order By: Relevance
“…27 Survival and retention in care in our study population was much higher than that observed from a pilot program at an urban hospital in Kampala, Uganda, 14 and a rural district in Malawi. 28 Survival in our study was likely overestimated.…”
Section: Discussioncontrasting
confidence: 60%
“…27 Survival and retention in care in our study population was much higher than that observed from a pilot program at an urban hospital in Kampala, Uganda, 14 and a rural district in Malawi. 28 Survival in our study was likely overestimated.…”
Section: Discussioncontrasting
confidence: 60%
“…and 62% at 6, 12 and 24 months respectively (Rosen, Fox, & Gill, 2007). One previous study from an informal settlement in Kenya, found that 29% of the patients discontinued ART (Unge, et al, 2009).…”
Section: Introductionmentioning
confidence: 92%
“…TASO worked with the Ugandan military to provide secure transportation of patients from rural areas to the main TASO site, when necessary. Although many programs in Africa are affected by considerable loss to follow-up [47], TASO compensates for this by employing a special counseling and home-based care team on motorcycles to consistently track patients. Motorcycles represent an important step forward in delivering care in rural regions because they can quickly traverse over diffi cult conditions, require only one rider (thus saving on driver costs), and can be relatively easily maintained.…”
Section: Communicationsmentioning
confidence: 99%